1988
DOI: 10.1002/jat.2550080303
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin adducts in animals exposed to gasoline and diesel exhausts 1. Alkenes

Abstract: Blood samples from rats and hamsters exposed to automotive engine exhausts in the Committee of Common Market Automobile Constructors long-term inhalation study at Battelle-Geneva were analysed for the levels of 2-hydroxyethylvaline (HOEtVal) and 2-hydroxypropylvaline (HOPrVal) in hemoglobin (Hb). These adducts to the N-terminus of the Hb chains were determined by gas chromatography-mass spectrometry of derivatives obtained by a modified Edman degradation that specifically cleaves off alkylated N-terminal amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Globin was precipitat ed according to the method described by Mowrer et al (14). The samples were anal yzed by gas chromatography-mass spectrometr y with respect to HOEtVal in hemo globin by an updated version (10) of the N-alkyl Edman method (4). For practical reasons, the samples from the referents were collected one month later than the sample s from the exposed persons, but replicate blood sampl es from two of the exposed persons were collected at the same time as the reference samples.…”
Section: Subj Ects and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globin was precipitat ed according to the method described by Mowrer et al (14). The samples were anal yzed by gas chromatography-mass spectrometr y with respect to HOEtVal in hemo globin by an updated version (10) of the N-alkyl Edman method (4). For practical reasons, the samples from the referents were collected one month later than the sample s from the exposed persons, but replicate blood sampl es from two of the exposed persons were collected at the same time as the reference samples.…”
Section: Subj Ects and Methodsmentioning
confidence: 99%
“…The adduct level in smokers [an increment of about 85 pmol/g Hb and 10 cigarettes/d (7») ind icat es that the ethene in tob acco smoke may be the source. This hypothesis is based on the assumption that human s and experimental anim als metabolize inhaled ethene to ethylene oxide (8)(9)(10) and detoxify ethylene oxide (see references II and 12) at approximat ely equal rat es or that the ratio of the rates of bioa ctivat ion and epoxide detox ification is approximatel y the same for man and rodents, with the same epoxide dose per milligram of inhaled ethene as a consequence (5).…”
mentioning
confidence: 99%
“…Tornqvist et al (15) demonstrated in rats and hamsters that exposure to automotive engine exhausts resulted in a doserelated increase of HEV in globin. In a recent study, we have demonstrated that bus garage workers and mechanics exposed to exhaust fumes have a higher HEV adduct level in globin (33.3 pmol/g globin) than a control population (22.1 pmol/g globin) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine (5 Ill) was added to neutralize the samples. Pentafluorophenyl isothiocyanate (7 Ill) was added, and the samples were then derivatized by incubation overnight at room temperature (23,24). The samples were extracted with ether, and the extracts evaporated to dryness under nitrogen, redissolved in toluene, and washed with 0.1 M disodium carbonate and water.…”
Section: Methodsmentioning
confidence: 99%
“…The pentafluorophenylthiohydantoins of hydroxyethylvaline and its de ute rated analogue were monitored at m/z 348 (M-HF)-' and 352, respectively. Calibration was carried out as described by Tornqvist et al (23).…”
Section: Methodsmentioning
confidence: 99%